2021
DOI: 10.1212/cpj.0000000000001028
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Access to Neurologic Telemedicine During the COVID-19 Pandemic

Abstract: Abstract:Objective:To determine whether there is a disparity in access to telemedical care that may be a function of socioeconomic status, language, or other demographic factors during the peak of the COVID-19 pandemic at a highly impacted urban center (Montefiore Medical Center) in Bronx, NY.Methods:We retrospectively investigated potential patient characteristics that might be associated with an increased likelihood of receiving a telephone visit as opposed to a televideo visit for patients followed in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 6 publications
4
17
0
Order By: Relevance
“…However, other studies also found that older persons were more likely to use telehealth than younger people [2,8]. Additionally, we found that the preference for telehealth among older patients was driven by telephone rather than video visits, which has been seen in studies of the general population as well [4,6,8,24]. Older patients' preference of telehealth over inperson visits could have resulted from early and persistent news coverage highlighting the risk of severe COVID-19 disease among older persons with comorbidities, as well as the unclear risk of contracting SARS-CoV-2 infection for PwH [25].…”
Section: Discussionsupporting
confidence: 57%
“…However, other studies also found that older persons were more likely to use telehealth than younger people [2,8]. Additionally, we found that the preference for telehealth among older patients was driven by telephone rather than video visits, which has been seen in studies of the general population as well [4,6,8,24]. Older patients' preference of telehealth over inperson visits could have resulted from early and persistent news coverage highlighting the risk of severe COVID-19 disease among older persons with comorbidities, as well as the unclear risk of contracting SARS-CoV-2 infection for PwH [25].…”
Section: Discussionsupporting
confidence: 57%
“…A video consultation was predicted to have enabled clinician goal achievement in 13 instances, bringing the total clinician success rate to 76/101 for all new consultations. However, some factors driving unsuccessful telephone consultations (particularly increasing age and lower socioeconomic status) will likely impair video consultations [11,12]. Future work comparing face-to-face, telephone and video consultations across all demographics and disease types is now required.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid adaptation of telemedicine in child neurology care due to the COVID-19 pandemic has been assessed in several studies, 13,15,[20][21][22][23][24][25] but beyond the initial implementation, the impact on care had not been fully assessed. Analyzing trends of telemedicine, a heterogeneous picture emerges with regards to patients suitable for telemedicine care and the effects of health disparities.…”
Section: Discussionmentioning
confidence: 99%